1986
DOI: 10.1002/art.1780290412
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil reduces progression of established renal disease in (NZB × NZW)F1 mice and delays renal disease in BXSB and MRL/1 strains

Abstract: Previous studies have shown that dietary marine lipids containing large quantities of n-3 polyunsaturated fatty acids, administered to (New Zealand black X New Zealand white)F1 and MRL-lpr/lpr mice before the development of renal disease, reduce the severity of glomerulonephritis in mice of these strains. The present stud,y demonstrated that delayed administration of a marine lipid diet, 25% menhaden oil (MO) by weight, until after the onset of overt renal disease, also resulted in significant improvement in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(37 citation statements)
references
References 26 publications
3
31
2
1
Order By: Relevance
“…This finding is in agreement with a recent study by Robinson et al [12]. Our results differ from the prolonged survival and decreased titers for anti-DNA antibody observed in NZB/NZW F, and BXSB mice [5,12,23] when given a diet with 25% menhaden oil as compared to beef tallow, high in saturated fatty acids. Kelley et al [14] als found increased life span and improved renal histology in Mrl/1 mice when given 20% menhaden oil compared to safflower oil.…”
Section: Discussioncontrasting
confidence: 53%
“…This finding is in agreement with a recent study by Robinson et al [12]. Our results differ from the prolonged survival and decreased titers for anti-DNA antibody observed in NZB/NZW F, and BXSB mice [5,12,23] when given a diet with 25% menhaden oil as compared to beef tallow, high in saturated fatty acids. Kelley et al [14] als found increased life span and improved renal histology in Mrl/1 mice when given 20% menhaden oil compared to safflower oil.…”
Section: Discussioncontrasting
confidence: 53%
“…Beneficial effects of EPA con centrate from fish oil (FO) were shown on some renal dis eases such as IgA nephropathy and renal transplantation [3][4][5], In 1981, Prickett et al [6] demonstrated that dietary supplementation with FO suppressed the manifestation of nephritis and prolonged survival in NZB/W FI mice. Similar effects were seen in other animal models of autoimmune nephritis such as BXSB mice [7] and MRL/ lpr mice [8]. Moreover, the administration of EPA has been reported to prevent or improve nephrotoxic serum nephritis and Heymann nephritis in rats [9,10].…”
Section: Introductionsupporting
confidence: 54%
“…When fish oil sup plementation was used in several different strains of lupus-prone mice, reductions in glomerular inflamma tion, proteinuria, and mortality were seen [43][44][45]. Even when fish oil supplements are begun after the onset of lupus nephritis, less severe nephrosclerosis is seen [46]. In adriamycin-induced nephrotic syndrome in rats, a small beneficial effect of fish oil supplementation has also been described [47], It should be noted, however, that in other models of kidney disease, the results of the use of fish oils have been less clear.…”
Section: Omega-3 Fatty Acid (Fish Oil) Supplementationmentioning
confidence: 99%